Learning Needs as a Reflection of Professional Interests among Health Experts - N. G. Goloenko; R. I. Yagudina; A. Yu. Kulikov; V. G. Serpik; M. V. Protsenko; P. A. Logvinyuc (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2019)
Eurasian Economic Union claims single rules for pharmaceutical circulation it will the ground for organizing the single pharmaceutical market. Because of such changes all the specialist from pharmaceutical market have to know all the new legislations. For the purpose of raise the organization responsibilities for quality and safety pharmaceuticals. Market autorotation holder have to create pharmacovigilance system. In connection with it the framework of the social survey was to find out the educational needs in pharmacovigilance among the health experts. The results of polling showed that experts had diffi culties in preparing pharmacovigilance documents. Major of the pollees expressed a wish to complete educational training which will be dedicated to the system of pharmacovigilance. The social survey results shows: converts educational needs among the pollees from 23 to 65 %, it points that experts want to get more additional information and some practical cases for understanding some issues in pharmacovigilance system through workshops, educational programs.